(untitled) (Informatica, 2021)
Stereoscopic lighting is one of the essential visual quality factors affecting the presentation of ceramic exhibits. This research adopted the method of bidirectional verification：psychophysical experiment and virtual environment with eye-movement tracking. We proposed a special questionnaire for the stereoscopic visual experience, obtained the nonlinear equations of the different volumes of exhibits. The eye-tracking data show that the visual fixation duration with stereoscopic lighting is (M=5.18s), and the number of fixation points accounted for 63.48% of the whole number. Both indexes were higher than the situation without stereoscopic lighting. The result shows that the accuracy of finding the detail changes with or without stereoscopic lighting was 12.5% through the comparison of visual identification tasks, and finding modeling changes was 11.5%. In the situation with stereoscopic lighting, the first identification frequency increased by 15.9% for small pattern changes of exhibits, as for local modeling changes increased by 19%. These results indicated that the stereoscopic lighting set according to the exhibits’ volume could effectively improve the viewer’s visual guide, strengthen the visual attention of the details, and model elements of the exhibits to achieve the optimal appreciation. These findings should contribute to offer critical insights into its evaluation and elaborate measurement. stereoscopic sense lighting, virtual environment, eye-movement tracking, ceramic exhibit